2024
DOI: 10.1186/s12889-023-17534-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunisation coverage and factors associated with incomplete immunisation in children under two during the COVID-19 pandemic in Sierra Leone

Myrte Wassenaar,
Augustin E. Fombah,
Haily Chen
et al.

Abstract: Background Routine childhood immunisation is one of the most important life-saving public health interventions. However, many children still have inadequate access to these vaccines and millions remain (partially) unvaccinated globally. As the COVID-19 pandemic disrupted health systems worldwide, its effects on immunisation have become apparent. This study aimed to estimate routine immunisation coverage among children under two in Sierra Leone and to identify factors associated with incomplete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…9 This is consistent with a recent study on immunisation in Sierra Leone, which saw a higher likelihood of missed vaccination for children with Muslim caregivers compared to children with Christian caregivers. 26 While these findings might not be consistent with all Muslims, it is believed that vaccine hesitancy and rejection among Muslims might be connected to whether vaccines are 'halal' (religiously permissible) or in line with Islamic teachings, particularly during the month of Ramadan. 12,[36][37][38] Previous evidence from Nigeria showed that tensions between Muslims and Christians may be a contributing factor, since vaccines mostly come from Christian nations.…”
Section: Cummings Et Al (2023) Conducted a Study On Vaccine Uptake Am...mentioning
confidence: 96%
See 2 more Smart Citations
“…9 This is consistent with a recent study on immunisation in Sierra Leone, which saw a higher likelihood of missed vaccination for children with Muslim caregivers compared to children with Christian caregivers. 26 While these findings might not be consistent with all Muslims, it is believed that vaccine hesitancy and rejection among Muslims might be connected to whether vaccines are 'halal' (religiously permissible) or in line with Islamic teachings, particularly during the month of Ramadan. 12,[36][37][38] Previous evidence from Nigeria showed that tensions between Muslims and Christians may be a contributing factor, since vaccines mostly come from Christian nations.…”
Section: Cummings Et Al (2023) Conducted a Study On Vaccine Uptake Am...mentioning
confidence: 96%
“…25 Many children either missed out on routine vaccination or never received the recommended doses of vaccines such as meases. 26 authorities. For example, the disproportionate use of power to enforce compliance during public health responses to health emergencies has been shown to severely impact access and demand for both routine and emergency vaccines.…”
Section: Impact Of Health Emergenciesmentioning
confidence: 99%
See 1 more Smart Citation